ANALISIS BEBAN KERJA PADA BAGIAN PRODUKSI PAVING GUNA MENGOPTIMALKAN JUMLAH PRODUKSI PADA PT. PESONA ARNOS BETON DI GRESIK - Ramadani, Brian; Khoiroh, Siti Muhimatul (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
PT Pesona Arnos Beton is a manufacturing company that produces paving products in Kedamean Hamlet, Karangandong District, Gresik Regency, East Java. The company produces 8 variants with different shapes and sizes. The company has a total of 5 paving machines with a total of 20 paving production workers. The production of paving in this company uses a make to stock system with a lead time so that there is more inventory and fast handling if there is an unexpected demand usually from a new housing project from the Gresik area and its surroundings that come directly to the factory, the level of inventory depends on the amount of paving made in each day. In this study the authors took the object of Workload Measurement Analysis with theiWorkload Analysis Method (WLA) in the Production section because this method is a suitable method to be used in measuring workload. Fromithe resulti of dataiprocessing, the minimum cost production capacity planning results are with production planning in a 6-month period using 20 workersiand producing 51150 paving pallets witia totalicost of Rp.462,861,000 per 6 months. Calculation of additional production capacity using overtime targets with an additional 1 working houriresulted inithe company incurring considerableicosts, where theicalculation results amounted to Rp.533,200,000 per 6 months